Complete chloroplast genome of the medicinal plant Amomum compactum: gene organization, comparative analysis, and phylogenetic relationships within Zingiberales - Ming-li Wu; Qing Li; Jiang Xu; Xi-wen Li (BMC, 2018)
Abstract Background Amomum compactum is one of the basic species of the traditional herbal medicine amomi fructus rotundus, with great pharmacology effect. The system position of A. compactum is not clear yet, and the introduction of this plant has been hindered by many plant diseases. However, the correlational molecular studies are relatively scarce. Methods The total chloroplast (cp) DNA was extracted according to previous studies, and then sequenced by 454 GS FLX Titanium platform. Sequence assembly was complished by Newbler. Genome annotation was preformed by CPGAVAS and tRNA-SCAN. Then, general characteristics of the A. compactum cp genome and genome comparsion with three Zingiberaceae species was analyzed by corresponding softwares. Additionally, phylogenetical trees were reconstructed, based on the shared protein-coding gene sequences among 15 plant taxa by maximum parsimony (MP) and maximum likelihood (ML) methods. Results The A. compactum cp genome with a classic quadripartite structure, consisting of a pair of reverse complement repeat regions (IRa/IRb) of 29,824 bp, a large single copy (LSC, 88,535 bp) region as well as a small single copy (SSC, 15,370 bp) region, is 163,553 bp in total size. The total GC content of this cp genome is 36.0%. The A. compactum cp genome owns 135 functional genes, that 113 genes are unique, containing eighty protein-coding genes, twenty-nine tRNA (transfer RNA) genes and four rRNA (ribosomal RNA) genes. Codon usage of the A. compactum cp genome is biased toward codons ending with A/T. Total 58 SSR loci and 24 large repeats are detected in the A. compactum cp genome. Relative to three other Zingiberaceae cp genomes, the A. compactum cp genome exhibits an obvious expansion in the IR regions. In A. compactum cp genome, the ycf1 pseudogene is 2969 bp away from the IRa/SSC border, whereas in other Zingiberaceae species, it is only 4-5 bp away from the IRa/SSC border. Comparative cp genome sequences analysis of A. compactum with other Zingiberaceae reveals that the gene order and gene content differ slightly among Zingiberaceae species. The phylogenetic analysis based on 67 protein-coding gene sequences supports the phylogenetic position of A. compactum. Conclusions The study has identified unique features of the A. compactum cp genome which would be helpful for us to understand the cp genome evolution and offer useful information for phylogenetics and further studies of this traditional medicinal plant.